Now crab sticks from carp - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The Japan International Research Center for Agricultural Sciences (JIRCAS) reports on how the flesh of carp raised in fish farms can be processed into surimi (crab sticks). Surimi is a preserved food hitherto made from the Alaska pollack fish.Japan...